International connectivity and the digital divide in Sub-Saharan Africa - (:unkn) unknown (My University, 2021)
In recent decades, international connectivity has improved significantly with the worldwide deployment of some 400 fiber submarine cables (SMCs), transmitting more than 99% of international telecommunications. If sub-Saharan African (SSA) has long remained excluded from this interconnection process, the maritime infrastructure network has recently densified and spurred an African connectivity catch-up. This paper estimates the impact of SMC deployment on the digital divide in a sample of 45 SSA countries covering the period of 1990–2014. Difference in differences (DID) estimations are conducted and highlight the particular contribution of SEACOM and EASSy cables, laid in 2009–2010, to Internet penetration in Eastern and Southern Africa. According to DID estimates, the rollout of these SMCs has yielded a 3–5 percentage point increase in Internet penetration rates in this region compared to the rest of SSA. This is a remarkable advancement, since this variation corresponds approximately to the level of Internet penetration in the subcontinent prior to their arrival.
Keywords: African Research